A review of physical, chemical, and biological green tide prevention methods in the Southern Yellow Sea. (July 2022) - Xia, Zhangyi; Yuan, Huanqing; Liu, Jinlin; Sun, Yuqing; Tong, Yichao; Zhao, Shuang; Xia, Jing; Li, Shuang; Hu, Meijuan; Cao, Jiaxing; Zhang, Jianheng; He, Peimin
Abstract: Green tides dominated by Ulva prolifera have be present in the Southern Yellow Sea for 15 consecutive years. They not only damage the marine environment, but also cause economic losses to coastal cities. However, there is still no fully effective approach for preventing green tides. In this article, approaches for the prevention of U . prolifera taken over recent years are reviewed. They can be generally divided into physical, chemical, and biological approaches. Physical approaches have been used to control the overwhelming green macroalgae bloom and inhibit the germination of U . prolifera, including physical salvage approach, refrigeration net technology, improved farming methods and raft technology, and modified clay method. These approaches require significant labor and material resources. Many chemical reagents have been used to eliminate U . prolifera early germination and growth, such as oxidative algaecide, acid treatment, heavy metal compounds, antifouling coating, and alkaloids. Chemical approaches have high efficiency, high economic benefit, and simple operation. Presently, biological control approaches remain in the exploratory stage. The verification of pilot and large-scale experiment results in sea areas is lacking, including the application of large organisms and microorganisms to control U . prolifera, and some of the mechanisms have not been thoroughly studied. This article introduces the three types of approaches, and evaluates the advantages and disadvantages of different methods to facilitate the reduction of the green tide bloom scale in the Southern Yellow Sea. Highlights: Introduction of physical, chemical, and biological methods of green tide prevention. Advantages and disadvantages of each method were evaluated. Recommendations for further research on Ulva prolifera prevention provided.